REIKI FOR DYSMENORRHEA MANAGEMENT: A PILOT STUDY - (:unkn) unknown (CARBONE EDITORE, 2019)
Introduction: This study was conducted to determine whether reiki is effective for managing dysmenorrhea. Materials and methods: The participants were asked to fill in a questionnaire form consisting of 10 questions and the McGill Pain Questionnarie before and after the reiki session. The reiki was performed by placing the hands over the seven main chakras and painful regions of the participants for a period of 30-45 minutes. Results: A statistically singnificant difference was found in the pain felt in the regions pre- and post-reiki application (p<0.001). The average pain score of the women was 3.85 prior to the reiki while it was 1.6 after the application, and there was a statistically significant difference between the average scores (p<0.001). Conclusions: 30-45 minutes of reiki had a positive effect on dysmenorrhea management.
Keywords: Dysmenorrhea; reiki; student; pain; COMPLEMENTARY